Application Counseling Cognitive Behavioral With Modeling Techniques In Setting Lesson Study To Invervene Self Aggresion In Class X MIA 1 Students Of SMA N 1 Sukasada - Indah Safitri (Department of Guidance and Counseling, FIP, Undiksha, 2018)
This study aims to determine the effectiveness of cognitive behavioral counseling with Modeling techniques in lesson study settings to intervene in student self-aggresion. The experimental design used was Pretest Postest Control Group Design. The sample of this study was class X MIA 1 SMA Negeri 1 Sukasada which was taken randomly from 6 class members of the population. The self aggresion data collection in this study used the Self Aggresion questionnaire. Hypothesis testing is carried out using the t-test. The results of the t-test obtained by thit amounted to 15.20 with a significance of <0.001. It identified that cognitive behavioral counseling with Modeling techniques in effective lesson study settings to intervene in self aggresion of students X MIA 1 Sukasada 1 Public High School.